A Generalization of the Fuglede-Putnam Theorem to Unbounded Operators. (25th March 2015) - Paliogiannis, Fotios C.
Abstract : Let N, M be unbounded normal operators in a Hilbert space and let T be a closed operator whose domain D ( T ) contains the domain of N, and the domain D ( T * ) contains the domain of M . It is shown that if T N ⊆ M T, then T N * ⊆ M * T .